Power in psychiatry: Soviet peer and lay hierarchies in the context of political abuse of psychiatry - Schacht, Anastassiya (History of psychiatry, 2022)
Soviet political abuse of psychiatry in the Brezhnevite era offers a rich case study of entanglement between various layers, impact spaces, and actors of power. This article discusses two types of discursive power in Soviet psychiatry. One sprang from the madness-affirmative cultural canon, in which dissidents sought their self-legitimation. More prominently, there was the power of psychiatrists within their own hierarchic system. I analyse how the action scopes for psychiatric power varied, depending on whether the recipient was a patient or fellow professional. Here, the inherent hierarchy structured and regulated the peer community and secured the stability of medical practices - and of the political entanglement of these practices and actors with the state-owned places of power.
Online veröffentlicht: 1. Oktober 2021
Gesehen am 21.10.2024